If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + -4 = 2 Reorder the terms: -4 + 3a = 2 Solving -4 + 3a = 2 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 3a = 2 + 4 Combine like terms: -4 + 4 = 0 0 + 3a = 2 + 4 3a = 2 + 4 Combine like terms: 2 + 4 = 6 3a = 6 Divide each side by '3'. a = 2 Simplifying a = 2
| 36-3(4r-8)=0 | | 247*.50= | | 14-2n= | | 1x+4y=-4 | | 0.5x+10=2.4x+3.4 | | 14a+16b+3c+5c-2b-6a= | | 5(x-6)=26-2x | | 10-(6)=2x | | X+x+1+x+2+x+3=132 | | 6x-4=74-7x | | (x-5)(-3x+7)-(x-5)=0 | | -17=-8 | | x^2+6x=x+3 | | 5y-6=2y+10 | | (X+8)+x=6 | | 8+2(x-2)=8 | | 6s-2t+3+7s+5t-9= | | 5x+39= | | 37+w=5w-2 | | X=2y-550 | | 9x+15=(3x+5) | | (8+10)-10=2x | | 2x-5y=-24 | | (X+8)+x=8 | | 3(e+1)=2(e-5) | | 84x^3-84x^2+84x-84=0 | | -63=-7x-9y*-7 | | -43x-23=15-72x | | 3sinx-2=-3 | | 36x-108=36+36x | | 5g+6+7g-10= | | vsquared+6v-16=0 |